Human Rights Activism for Democracy and Human Development in the Democratic Republic of Congo: A Conceptual Appraisal - Mbecke, P. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
Debates on the impact of democracy on human development are controversial depending on the theory in use. Through the combination of the democratic theory on good governance and public administration and human development research approaches on service delivery, this paper aims to show that dictatorship and government’s lethargy to embark on democratic process and good governance have hampered the development of the Democratic Republic of Congo. Considering the escalating human rights abuses and violence linked to elections and electoral processes, denying or delaying people’s right to elections not only falsifies democracy but contributes to underdevelopment. The paper emphasises that democracy can favour development. It recommends that establishing both democracy and good governance can foster development in the one hand and an effective and responsible human rights activism can hold the government of the Democratic Republic of Congo accountable in implementing democratic processes and good governance for service delivery resulting in human development in the other hand.
Journal article published in the International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Democracy; Elections; Human development; Human rights activism; Human rights - Developing countries; Democratic Republic of Congo -Politics and government